How civility works - Bybee, Keith J., 1965- (Stanford Briefs, an imprint of Stanford University Press, 2016)
Is civility dead? Americans ask this question every election season, but their concern is hardly limited to political campaigns. Doubts about civility regularly arise in just about every aspect of public life. Rudeness runs rampant. Our news media is saturated with aggressive bluster and vitriol. Our digital platforms teem with expressions of disrespect and trolls. Reflecting these conditions, surveys show that a significant majority of Americans believe we are living in an age of unusual anger and discord. Everywhere we look, there seems to be conflict and hostility, with shared respect and consideration nowhere to be found. In a country that encourages thick skins and speaking one's mind, is civility even possible, let alone desireable?